2017
DOI: 10.1523/jneurosci.1378-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Double-Strand Breaks in Oligodendrocytes Cause Demyelination, Axonal Injury, and CNS Inflammation

Abstract: Mitochondrial dysfunction has been implicated in the pathophysiology of neurodegenerative disorders, including multiple sclerosis (MS). To date, the investigation of mitochondrial dysfunction in MS has focused exclusively on neurons, with no studies exploring whether dysregulation of mitochondrial bioenergetics and/or genetics in oligodendrocytes might be associated with the etiopathogenesis of MS and other demyelinating syndromes. To address this question, we established a mouse model where mitochondrial DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 62 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…The exact mechanisms behind this remain unclear; however, several essential pathways involved in DNA damage and repair, the epigenetic machinery and metabolic processes might be involved. The higher occurrence of oxidative DNA damage and impaired repair compared to other CNS cell types, challenge the genomic stability of OPCs [ 51 , 123 , 124 ]. Furthermore, ROS can negatively impact DNA methylation, histone acetylation, and miRNA presence, which are all deemed necessary in OPC differentiation and especially relieving its blocking mechanisms [ 26 , 125 , 126 , 127 , 128 ].…”
Section: Sphingosine-1-phosphate Receptors and Multiple Sclerosis mentioning
confidence: 99%
“…The exact mechanisms behind this remain unclear; however, several essential pathways involved in DNA damage and repair, the epigenetic machinery and metabolic processes might be involved. The higher occurrence of oxidative DNA damage and impaired repair compared to other CNS cell types, challenge the genomic stability of OPCs [ 51 , 123 , 124 ]. Furthermore, ROS can negatively impact DNA methylation, histone acetylation, and miRNA presence, which are all deemed necessary in OPC differentiation and especially relieving its blocking mechanisms [ 26 , 125 , 126 , 127 , 128 ].…”
Section: Sphingosine-1-phosphate Receptors and Multiple Sclerosis mentioning
confidence: 99%
“…Mitochondrial abnormalities and energy failure promote increased demyelination and inflammation in neurons and tissues affected by MS, exacerbating the disease. MtD can cause primary oligodendropathy, triggering demyelination . Also, MtD has been found to play a key role in a progressive axonal loss in MS .…”
Section: Elucidation Of the Role Of Oxidative Stress (Os) And Mitochomentioning
confidence: 99%
“…MtD can cause primary oligodendropathy, triggering demyelination. 34 Also, MtD has been found to play a key role in a progressive axonal loss in MS. 17,35,36 Following axonal demyelination in MS, it has been hypothesized that mitochondria play a greater role in maintaining axonal function as an adaptive process to the increased energy need of demyelinated axons but MtD results over time leading to severe and chronic axonal damage. 35,37,38 F I G U R E 1 The role of mitochondria dysfunction and oxidative stress in MS | 307 TOBORE Aside from MtD, OS plays a role in demyelination and axonal damage in MS. [39][40][41][42] Findings from several studies have suggested that OS plays the most important role in the demyelination and neurodegeneration observed in MS. [42][43][44][45][46] OS causes selective oligodendrocyte death and can disrupt the process of oligodendrocyte differentiation, leading to demyelination.…”
Section: Neurodegeneration Demyelination and Axonal Loss In Msmentioning
confidence: 99%
“…1). 41,[59][60][61][62][63][64][65][66][67][68] Although a principal role of mitochondria is to supply the bioenergy needed for cellular processes and maintenance, 69-71 mitochondria also help regulate neurite branching and regeneration as well as synaptic strength, stability, and signaling in the CNS. 72 In addition, myelin repair is intimately dependent on healthy mitochondrial function within the CNS in oligodendrocytes and neuronal cell bodies.…”
Section: Introductionmentioning
confidence: 99%
“…72 In addition, myelin repair is intimately dependent on healthy mitochondrial function within the CNS in oligodendrocytes and neuronal cell bodies. 63,64,[73][74][75][76][77] Dysfunctional mitochondria become sources of reactive oxygen species (ROS) that contribute to OS with deleterious effects on the cell's wellbeing. 61,70,71,74,[77][78][79][80] Manifestations of OS are hallmark symptoms in neurological disease, including cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%